Effects of DLP printing orientation and postprocessing regimes on the properties of 3D printed denture bases - Jafarpour, Dana; El-Amier, Nesma; Tahboub, Kawkab; Zimmermann, Elizabeth; Pero, Ana Carolina [UNESP]; de Souza, Raphael (Elsevier, 2025)
Statement of problem: The variety of recommended postprocessing techniques and printing parameters makes it challenging to determine the best approach to 3-dimensionally (3D) printed dentures. Purpose: The purpose of this in vitro study was to assess the effect of printing orientations (0, 45, and 90 degrees) and postprocessing treatments (ultraviolet [UV], heat, or combination) on the mechanical and surface properties of 3D printed denture base resin. Material and methods: Three-dimensionally printed denture base resin specimens were fabricated at 0-, 45-, and 90-degree printing orientations, followed by 4 postprocessing techniques (UV, Heat, UV+Heat, and control). Microhardness was assessed using a Vickers microhardness tester. Additionally, the flexural strength (FS) and modulus of elasticity (MoE) were analyzed using a 3-point bend test. Wettability was measured according to the sessile drop test. The fractured surfaces were observed under scanning electron microscopy (SEM). Results: FS was significantly greater (P<.001) at a print orientation of 90 degrees (73.7 MPa) compared with 0 and 45 degrees (55.2 and 61.8 MPa). No significant difference in FS was found among postprocessing treatments (all complied with the International Organization for Standardization [ISO] requirements). The UV group had the highest MoE (up to 2061 MPa), followed by the heat-treated groups (up to 1412 MPa). The 45-degree print orientation showed the highest contact angle (CA) in almost all groups (CA=117.6±11.7), and UV led to higher hydrophilicity (CA=33.9±12.0). The effect of build orientation on the microhardness depended on the postprocessing technique with the highest value (23.4 ±1.3) achieved by UV postprocessing in combination with the 90-degree orientation. Conclusions: The optimal FS of 3D printed denture base resin is achieved when it is printed in a vertical orientation (90 degrees relative to the platform base). Thermal annealing as a postprocessing technique combined with UV can effectively enhance FS, induce favorable wettability, and reduce stiffness.